Are we willing to share what we believe is true? Factors influencing susceptibility to fake news - Piksa, Michal; Noworyta, Karolina; Gundersen, Aleksander B.; Kunst, Jonas; Morzy, Mikolaj; Piasecki, Jan; Rygula, Rafal (Frontiers in Psychiatry, 2023)
Background: The contemporary media landscape is saturated with the ubiquitous presence of misinformation. One can point to several factors that amplify the spread and dissemination of false information, such as blurring the line between expert and layman's opinions, economic incentives promoting the publication of sensational information, the zero cost of sharing false information, and many more. In this paper, we investigate some of the mechanisms of fake news dissemination that have eluded scientific scrutiny: the evaluation of veracity and behavioral engagement with information in light of its factual truthfulness (either true or false), the cognitive utility (either enforcing or questioning participants’ beliefs), and the presentation style (either sober or populistic). Results: Two main results emerge from our experiment. We find that the evaluation of veracity is mostly related to the objective truthfulness of a news item. However, the probability of engagement is more related to the congruence of information with the participants’ preconceived beliefs than it is to the objective truthfulness or the presentation style of the information. Conclusions: We conclude that the common notion that the spread of fake news can be limited by factchecking and educating people might not be entirely true, as people will share fake information as long as it reduces the entropy of their mental models of the world. We also find support for the Trojan horse hypothesis of fake news dissemination.